Job Characteristics - Evolution of the Theoretical Framework and Practical Applications - Rymaniak, Janusz; Rymaniak, Janusz (Studia Oeconomica Posnaniensia, 2013)
The author presents the concept of job characteristics proposed by Oldham and Hackman, being an extension of Herzberg's concept of two-factor motivation. The original JCM model has been expanded by the addition of other concepts and tools, and transformed into theory. This paper presents an analysis of the subject literature and various avenues of methodological research as well as the practical applications of the model developed in the years 2000-2012.